The influence of added lysine during lactation on sow and litter performance - Laurin, J.L.; Richard, R.D.; Keesecker, D.R.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An on-farm field study utilizing 287 crossbred sows was conducted to investigate the influence of additional dietary lysine during lactation on sow and litter performance. At farrowing, sows were randomly assigned to one of two milo-soybean meal diets containing either .65% (13.5 % CP) or .85% lysine (16.3% CP). Average sow parity was 3.75, and sows on both treatments had a similar number of pigs born alive and similar pig and litter birth weights. All litters were equalized to approximately 9.5 pigs within 24 hours following farrowing, and average lactation length was 21 d. No treatment x parity interactions were observed for any response criteria. Pig and litter weaning weights were increased from 13.10 and 114.7 to 13.65 and 120.9 lb for sows fed the .65% and .85% lysine diets, respectively. Pig survival was excellent for both groups of sows; however, survivability tended to be improved for 2nd and 4th parity sows fed the .85% lysine diet. Increased dietary lysine during lactation resulted in no difference for number days from weaning to estrus; however, the subsequent farrowing rate for the sows fed the .85% lactation diet was 75.7% as compared to 70.4% for the sows fed the .65% lysine diet. These results indicate that increased dietary lysine during lactation improved pig and litter weaning weights.
Keywords: Swine; Sow; Performance; Lactation; Lysine